Influences of inattention on perceived self-efficacy, stress, and depression - Carriere, Jonathan S. A.; Nelson, Andrea L.; Cheyne, James Allan; Smilek, Daniel (Frontiers in Cognition, 2023)
Introduction Going through life mindlessly appears to produce feelings of boredom and depression, suggesting that cognitive deficits can lead both directly and indirectly to emotional problems. Under this hypothesis, there are numerous possible routes from attention to affective issues, including through the sense of self-efficacy – a judgement about our ability to successfully achieve goals – and the experience of psychological stress. The present study assessed potential pathways from everyday inattentiveness, through the presumed intermediate experiences of diminished self-efficacy and psychological stress, to the experience of depressive affect. Method In two studies we collected questionnaire responses from large groups of participants (N = 188, Study 1; N = 399, Study 2), assessing individual differences in trait inattention, attention-related errors, self-efficacy, stress, and depression. Results Via path analyses we tested several predictions: 1) the frequency of attention lapses predicts depressive affect; 2) attention-related errors mediate effects of inattention in predicting both self-efficacy and stress; 3) self-efficacy and stress directly influence depressive affect. The results indicate the proposed Attention-to-Affect models provide good fit overall. They also indicate a reversal of the causal flow, while consistent with traditional views, does not adequately fit the data. Discussion That the Attention-to-Affect models provide good fit for the data is consistent with the view that everyday inattention contributes to the emotional distress that creates depression. While this view is contrary to the typical conception of attention problems as consequences of depression, it is consistent with our own previous findings. Accordingly, our results continue to suggest it is important for future research to further validate this pathway and to consider directly remedying attentional issues as a potentially important part of depression treatment strategies.